Insertion of an Ultrathin Interfacial Aluminum Layer for the Realization of a Hf0.5Zr0.5O2 Ferroelectric Tunnel Junction. Issue 10 (24th March 2022) - Manchon, Benoît; Segantini, Greta; Baboux, Nicolas; Rojo Romeo, Pedro; Barhoumi, Rabei; Infante, Ingrid C.; Alibart, Fabien; Drouin, Dominique; Vilquin, Bertrand; Deleruyelle, Damien
Abstract : Herein, the effect of a 2 nm thin aluminum layer inserted between the ferroelectric layer and the top electrode in a TiN/ Hf 0.5 Zr 0.5 O 2 /TiN stack deposited by reactive magnetron sputtering is investigated. The oxidation of the interfacial layer during annealing due to scavenging of the Hf 0.5 Zr 0.5 O 2 impacts both the ferroelectric properties and the electrical conductivity of the junction. It is shown that the overall conductivity of the junction is boosted 20 folds while the resistance ratio between the positive and negative polarization states is increased from 1.3 up to 3.7. Through a systematic analysis of programming conditions, pulse duration, and height, we show that both the remanent polarization and On/Off current ratio can be enhanced at the expanse of the endurance leading to a trade‐off. Abstract : Metal–insulator–ferroelectric–metal (MFIM) structure have recently been brought to the spotlight as a way to make Ferroelectric Tunnel Junction (FTJ) without the need for ultrathin ferroelectric layer. Herein, the first use of an ultrathin Al layer for the fabrication of an MFIM Hf 0.5 Zr 0.5 O 2 –based FTJ through the scavenging of oxygen from the oxide during annealing is presented.